Whole earth discipline why dense cities, nuclear power, transgenic crops, restored wildlands and geoengineering are necessary - Brand, Stewart., Author (Penguin, 2010)
"This eye-opening book by the author of the National Book Award-winning Whole Earth Catalog persuasively details a new approach to our stewardship of the planet. Lifelong ecologist and futurist Stewart Brand relies on scientific rigor to shatter myths concerning nuclear energy, urbanization, genetic engineering, and other controversial subjects, showing exactly where the sources of our dilemmas lie and offering a bold, inventive set of policies and design-based solutions for shaping a more sustainable society..."--P. [4] of cover.